Acute appendicitis: a 2- year review of clinical presentation and histopathology - Subedi, N; Dangol, US; Adhikary, MB; Pudasaini, S; Baral, R (Journal of Pathology of Nepal, 2011)
Background: Acute appendicitis is the most common surgical emergency. Obstruction of the lumen by fecolith is the usual cause of acute appendicitis.The aim of the study was to analyze clinical presentation of acute appendicitis and its histopathological correlation. Materials and Methods: A retrospective study of acute appendicitis was done in the Department of Surgery of Helping Hands Community Hospital from January 2009 to December 2010. Three hundred forty five patients out of 415 patients with clinical diagnosis of appendicitis underwent operative treatment. The histopathological reports were reviewed and correlated with clinical diagnosis. Results: Out of 345 patients who underwent operative procedure 98% (n= 338) came with chief complaint of pain in the periumbilical region migrating to the right iliac fossa. The mean age of presentation was 42 years. Increased leucocyte count was seen in only 65% cases. Acute appendicitis was more commonly seen in male patients (214 cases, 62%). The most common per operative finding was acutely inflammed appendix (84%) followed by perforated appendix (7.5%), gangrenous appendix (3.5%) and appendicular lump (1.5%). However, histopathological diagnoses were acute appendicitis (91.9%), resolving appendicitis (3.5%), lymphoid hyperplasia (2.6%), mucocele (0.3%) and carcinoid (0.3%). Normal histology was seen in 1.4% cases. Conclusion: Though there are other causes of acute abdomen, acute appendicitis still stands first amongst all the emergencies. Histopathological examination of appendectomy specimen should not be omitted in order to see the incidence negative appendectomy rate and to avoid complications relating to malignant conditions. Keywords: Acute appendicitis; Appendectomy; Appendicular perforation; Histopathology DOI: http://dx.doi.org/10.3126/jpn.v1i2.5402 JPN 2011; 1(2): 104-107